Baicalein inhibits inflammatory response and promotes osteogenic activity in periodontal ligament cells challenged with lipopolysaccharides - Manman Ren; Ya Zhao; Zhiqi He; Jian Lin; Chuchu Xu; Fen Liu; Rongdang Hu; Hui Deng; Yi Wang (BMC, 2021)
Abstract Background Periodontitis is a chronic infection initiated by oral bacterial and their virulence factors, yet the severity of periodontitis is largely determined by the dysregulated host immuno-inflammatory response. Baicalein is a flavonoid extracted from Scutellaria baicalensis with promising anti-inflammatory properties. This study aims to clarify the anti-inflammatory and osteogenic effects of baicalein in periodontal ligament cells (PDLCs) treated with lipopolysaccharides (LPS). Methods Human PDLCs were incubated with baicalein (0-100 μM) for 2 h prior to LPS challenge for 24 h. MTT analysis was adopted to assess the cytoxicity of baicalein. The mRNA and protein expression of inflammatory and osteogenic markers were measured by real-time polymerase chain reaction (PCR), western blot and enzyme-linked immunosorbent assay (ELISA) as appropriate. Alkaline phosphatase (ALP) and Alizarin red S (ARS) staining were performed to evaluate the osteogenic differentiation of PDLCs. The expression of Wnt/β-catenin and mitogen-activated protein kinase (MAPK) signaling related proteins was assessed by western blot. Results MTT results showed that baicalein up to 100 μM had no cytotoxicity on PDLCs. Baicalein significantly attenuated the inflammatory factors induced by LPS, including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), matrix metalloprotein-1 (MMP-1), MMP-2 and monocyte chemoattractant protein 1 (MCP-1) at both mRNA and protein level. Moreover, MAPK signaling (ERK, JNK and p38) was significantly inhibited by baicalein, which may account for the mitigated inflammatory response. Next, we found that baicalein effectively restored the osteogenic differentiation of LPS-treated PDLCs, as shown by the increased ALP and ARS staining. Accordingly, the protein and gene expression of osteogenic markers, namely runt-related transcription factor 2 (RUNX2), collagen-I, and osterix were markedly upregulated. Importantly, baicalein could function as the Wnt/β-catenin signaling activator, which may lead to the increased osteoblastic differentiation of PDLCs. Conclusions With the limitation of the study, we provide in vitro evidence that baicalein ameliorates inflammatory response and restores osteogenesis in PDLCs challenged with LPS, indicating its potential use as the host response modulator for the management of periodontitis.